Calidad de servicio educativo e identidad institucional docente en el C.E.I.P.S.M.P. Sagrada Familia nivel primaria, Iquitos 2023 - Garcia Yumbato, Flavia Silvana (2024)
The study aimed to investigate the relationship between the quality of educational service and teacher institutional identity at the C.E.I.P.S.M.P Sagrada Familia, primary level, in Iquitos during 2023. A non-experimental, cross-sectional, field based, bivariate, and relational design was used. The total population was 30 teachers, with a sample of 16 teachers who answered validated questionnaires. Results and conclusion: The results showed a Spearman correlation coefficient (rho = .653), indicating a positive and moderate relationship between the studied variables. With a 95% confidence level, it was concluded that higher quality educational service is related to higher levels of institutional identity among teachers at the C.E.I.P.S.M.P Sagrada Familia, primary level, in Iquitos during 2023.